Seventeen new species and additional records of Lathrobium (Coleoptera, Staphylinidae) from mainland China - Peng, Zhong; Li, Li-Zhen; Zhao, Mei-Jun (Zootaxa, 2014)
Material of the paederine genus Lathrobium Gravenhorst, 1802 from the Chinese provinces Heilongjiang, Ningxia, Qinghai, Henan, Anhui, Zhejiang, Jiangxi, Hunan, Chongqing, Guizhou, Yunnan and Guangdong was examined. Twenty-one species were identified, seventeen of which are described as new: L. liuae (Heilongjiang: Hongwei); L. ningxiaense sp. n. (Ningxia: Heshangpu); L. baiyunense sp. n. (Henan: Baiyun Shan); L. ayui sp. n. (Anhui: Yaoluoping); L. yaoluopingense sp. n. (Anhui: Yaoluoping); L. chenae sp. n. (Zhejiang: Qingliangfeng); L. fengae sp. n. (Zhejiang: Qingliangfeng); L. gutianense sp. n. (Zhejiang: Gutian Shan); L. nannani sp. n. (Zhejiang: Gutian Shan); L. sanqingense sp. n. (Jiangxi: Sanqing Shan); L. badagongense sp. n. (Hunan: Badagong Shan); L. xui sp. n. (Chongqing: Huanggangou); L. fanjingense sp. n. (Guizhou: Fanjing Shan); L. lui sp. n. (Guizhou: Kuankuoshui); L. zhaigei sp. n. (Guizhou: Kuankuoshui); L. zizhiense sp. n. (Yunnan: Zizhi) and L. guangdongense sp. n. (Guangdong: Nanling). The female sexual characters of L. lingae Peng, Li & Zhao and L. longwangshanense Peng, Li & Zhao are described and illustrated for the first time. The junior primary homonym Lathrobium pilosum Peng & Li, 2012 is replaced with Lathrobium zhui nom. n. Including the new taxa described here, 189 Lathrobium species are currently known from the mainland China.